Effect of grain source and brewer's grain on the performance and serum cholesterol concentration of finishing steers - Goldy, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The inclusion of brewer's grains at 20% of the ration dry matter increased dry matter intake, resulting in poorer feed efficiency. Brewer's grain appeared to increase serum cholesterol. Serum cholesterol increased as days on feed increased, similar to other reported studies. Steers fed grain sorghum had greater dry matter intakes and poorer feed efficiencies than those fed barley or wheat. Analysis of tissue samples has not been completed at this time, which prohibits drawing any conclusions as to the effect on tissue cholesterol concentrations.
Keywords: Beef; Grain source; Brewer's grain; Performance; Serum cholesterol; Steers